Translation, adaptation and validation the contents of the Diabetes Medical Management Plan for the Brazilian context - Heloísa de Carvalho Torres; Fernanda Figueredo Chaves; Daniel Dutra Romualdo da Silva; Adriana Aparecida Bosco; Beatriz Diniz Gabriel; Ilka Afonso Reis; Júlia Santos Nunes Rodrigues; Adriana Silvina Pagano
ABSTRACT Objective: to translate, adapt and validate the contents of the Diabetes Medical Management Plan for the Brazilian context. This protocol was developed by the American Diabetes Association and guides the procedure of educators for the care of children and adolescents with diabetes in schools. Method: this methodological study was conducted in four stages: initial translation, synthesis of initial translation, back translation and content validation by an expert committee, composed of 94 specialists (29 applied linguists and 65 health professionals), for evaluation of the translated version through an online questionnaire. The concordance level of the judges was calculated based on the Content Validity Index. Data were exported into the R program for statistical analysis: Results: the evaluation of the instrument showed good concordance between the judges of the Health and Applied Linguistics areas, with a mean content validity index of 0.9 and 0.89, respectively, and slight variability of the index between groups (difference of less than 0.01). The items in the translated version, evaluated as unsatisfactory by the judges, were reformulated based on the considerations of the professionals of each group. Conclusion: a Brazilian version of Diabetes Medical Management Plan was constructed, called the Plano de Manejo do Diabetes na Escola.